Effective role of CaO/P(2)O(5) ratio on SiO(2)-CaO-P(2)O(5) glass system - Kiran, P. (J Adv Res, 2017)
In the present work, the effect of the CaO/P(2)O(5) ratio on the composition of sol-gel synthesized 58SiO(2)-(19 − x)P(2)O(5)–(23 + x)CaO (x = 0, 5, 10 and 15 mol%) glass samples was studied. Further, the effect of NBO/BO ratio on hydroxy carbonated apatite layer (HCA) forming ability based on dissolution behavior in simulated body fluid (SBF) solution was also investigated. CaO/P(2)O(5) ratios of synthesized glass samples were 1.2, 2, 3.6, and 9.5, respectively. NBO/BO ratios were obtained using Raman spectroscopic analysis as 0.58, 1.20, 1.46, and 1.78, respectively. All samples were soaked in the SBF solution for 7 days. The calculated weight losses of these samples were 58%, 64%, 83%, and 89% for corresponding NBO/BO ratios. The increase in CaO/P(2)O(5) ratio increases the NBO/BO ratios. However, the increase in NBO/BO ratio increases HCA forming ability of SBF treated samples. The HCA crystalline layer formation was confirmed through X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), Raman and Infrared spectroscopic analysis. Higher CaO/P(2)O(5) ratio favors the increase in HCA formation for SBF treated calcium phospho silicate glasses.